Use of α-cyclodextrin to Promote Clean and Environmentally Friendly Disinfection of Phenolic Substrates via Chlorine Dioxide Treatment - Chaudhuri, Sauradip; DiScenza, Dana J.; Boving, Thomas B.; Burke, Alan; Levine, Mindy (Frontiers in Chemistry, 2020)
The use of chlorine dioxide to disinfect drinking water and ameliorate toxic components of wastewater has significant advantages in terms of providing safe water. Nonetheless, significant drawbacks towards such usage remain. These drawbacks include the fact that toxic byproducts of the disinfection agents are often formed, and the complete removal of such agents can be challenging. Reported herein is one approach to solving this problem: the use of α-cyclodextrin to affect the product distribution in chlorine dioxide-mediated decomposition of organic pollutants. The presence of α-cyclodextrin leads to markedly more oxidation and less aromatic chlorination, in a manner that is highly dependent on analyte structure and other reaction conditions. Mechanistic hypotheses are advanced to explain the cyclodextrin effect, and the potential for use of α-cyclodextrin for practical wastewater treatment is also discussed.